Achieving Ultra-Broad Microwave Absorption Bandwidth Around Millimeter-Wave Atmospheric Window Through an Intentional Manipulation on Multi-Magnetic Resonance Behavior - Liu, Chuyang; Xu, Lu; Xiang, Xueyu; Zhang, Yujing; Zhou, Li; Ouyang, Bo; Wu, Fan; Kim, Dong‑Hyun; Ji, Guangbin (Nano-Micro Letters, 2024)
The utilization of electromagnetic waves is rapidly advancing into the millimeter-wave frequency range, posing increasingly severe challenges in terms of electromagnetic pollution prevention and radar stealth. However, existing millimeter-wave absorbers are still inadequate in addressing these issues due to their monotonous magnetic resonance pattern. In this work, rare-earth La3+ and non-magnetic Zr4+ ions are simultaneously incorporated into M-type barium ferrite (BaM) to intentionally manipulate the multi-magnetic resonance behavior. By leveraging the contrary impact of La3+ and Zr4+ ions on magnetocrystalline anisotropy field, the restrictive relationship between intensity and frequency of the multi-magnetic resonance is successfully eliminated. The magnetic resonance peak-differentiating and imitating results confirm that significant multi-magnetic resonance phenomenon emerges around 35 GHz due to the reinforced exchange coupling effect between Fe3+ and Fe2+ ions. Additionally, Mössbauer spectra analysis, first-principle calculations, and least square fitting collectively identify that additional La3+ doping leads to a profound rearrangement of Zr4+ occupation and thus makes the portion of polarization/conduction loss increase gradually. As a consequence, the La3+–Zr4+ co-doped BaM achieves an ultra-broad bandwidth of 12.5 + GHz covering from 27.5 to 40 + GHz, which holds remarkable potential for millimeter-wave absorbers around the atmospheric window of 35 GHz. Highlights: 1 The frequency and intensity of multi-magnetic resonance are freely regulated by co-doping La3+ and Zr4+ ions. 2 Zr4+ occupation is elaborately modified for promoting the portion of polarization/conduction loss to increase profoundly. 3 The optimized electromagnetic characteristics lead to an ultra-wide bandwidth of 12.5+ GHz around millimeter-wave atmospheric window.